A computer tool for the kinematic analysis of planar four- bar linkage (2015)
The fundamentals for the creation of graphic user interface to assist in the teaching of the Kinematics of all-revolute- oint planar four-bar linkages are presented. Using the Matlab® GUIDE tool, the very interactive GUI allows user input to change the link lengths, for example, through both numerical input from the mouse and variations with the computer mouse. It also lets the user to know the output values of any point along any element in the mechanism. Trying to enrich the technical vocabulary of the users, the original Spanish version of the GUI can be easily changed to English. Surveys of preliminary versions of the GUI were taken into account towards the GUI final version. Results were compared against similar limited softwares and documented cases. This is an undergraduate research project that pretends to spark the students’ interest in developing educational software as a business opportunity based on a future Android application.